PENGARUH TINGKAT PENDIDIKAN, UPAH MINIMUM, INVESTASI, DAN BIAYA PEMBANGUNAN INFRASTRUKTUR TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN - Ardiyanti, Ni Luh Gde Mitha; Suasih, Ni Nyoman Reni (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 7 (2023): Vol.12.7. JULI.2023[451-532], 2023)
This study aims to analyze the effect of education level, minimum wage, investment, and infrastructure development costs on the inequality of income distribution between districts / cities in Bali Province. The location of the study is in districts / cities in Bali Province with secondary data obtained from publications from the Central Statistics Agency, Public Works Office, Spatial Planning, Housing, and Settlement Areas of Bali Province. The number of observations of this study was 90 observations with a period of 10 years and involved 9 regencies/cities in Bali Province. Data collection method in this study through non-participant observation techniques. The analysis technique used is panel data regression analysis. The results of the panel data regression test showed that the most appropriate model was the random effect model (REM). The results of this study show that education level, minimum wage, investment, and infrastructure development costs simultaneously affect income distribution inequally. Partially, the variables of education level and minimum wage have a positive and significant effect, while investment and infrastructure development costs have a negative and insignificant effect on the inequality of income distribution between districts / cities of Bali Province. keyword : Education, Minimum Wage, Investment, Infrastructure, Income Distribution Klasifikasi JEL: I25, J3, E2, O1, D33